Tourism in the state of M’sila between reality and planning. A case study of the region and city of Bou Saada – Algeria - Barkat, Zine elabidine; Ghanem, Abdelghani (Technium Social Sciences Journal, 2023)
Nowadays, tourism has emerged as an industry and an opportunity that cannot be neglected. Many countries have accorded proper importance to tourism as a major contributor to the economy. Indeed, it is an effective mechanism for generating national dynamism in different infrastructures and creating new jobs (reducing unemployment rates). M’sila province in general, and Bou Saada city in particular, are known to be an excellent tourist destination. During the colonial period and after the independence, this region has witnessed an important influx of tourists from all over the world. However, the tourism sector in this region is so neglected that the number of arrivals have decreased considerably and have therefore damaged the attractive image of M’sila and Bousaada. This situation requires urgent interventions to revive tourism, and find solutions to all the issues identified.